2016
DOI: 10.1038/npp.2016.162
|View full text |Cite
|
Sign up to set email alerts
|

Lisdexamfetamine Effects on Executive Activation and Neurochemistry in Menopausal Women with Executive Function Difficulties

Abstract: Many women with no history of executive dysfunction report difficulties in this domain during the menopause transition. Lisdexamfetamine (LDX) has been suggested to be a safe and effective treatment option for these women. However, the mechanism by which LDX improves executive functioning in these women is not known. Here we investigated the effects of LDX on brain activation and neurochemistry, hypothesizing that LDX would be associated with increased activation and decreased glutamate in executive regions. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Specifically, gonadal steroids can have great impact on brain structure, function, regional connectivity, and neurochemistry [14], which influences executive functions, affect, and reward processing. The prefrontal cortex—the site of estrogen modulation of executive function—is essential for cognitive processes such as sustained attention, working memory, organization, and planning [14, 31, 62]. FTM individuals taking high-dose testosterone and left in a hypoestrogenic and hypertestosteronic state could be at risk for executive dysfunction, as exhibited in cisgender females experiencing premature loss of estradiol or polycystic ovary syndrome, respectively [63,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, gonadal steroids can have great impact on brain structure, function, regional connectivity, and neurochemistry [14], which influences executive functions, affect, and reward processing. The prefrontal cortex—the site of estrogen modulation of executive function—is essential for cognitive processes such as sustained attention, working memory, organization, and planning [14, 31, 62]. FTM individuals taking high-dose testosterone and left in a hypoestrogenic and hypertestosteronic state could be at risk for executive dysfunction, as exhibited in cisgender females experiencing premature loss of estradiol or polycystic ovary syndrome, respectively [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature in cisgender populations, it is known that estradiol, testosterone, and progesterone—as well as its neurosteroid metabolite allopregnanolone (Allo)—have strong influence on neurotransmitter levels and receptors, as well as neuronal and glial architecture and function in presumably cisgender individuals [14, 30, 31]. Since changes in these gonadal and adrenal steroid levels can profoundly affect cognition and mood [14, 32], exogenous hormone administration by GAHT must further be studied to better inform patients about potential changes in executive functioning and behavioral health.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, both estrogen and progestagens are neuromodulators, and have been shown to interact with neurotransmitters, including dopamine, serotonin, gamma‐aminobutyric acid, glutamate, and acetylcholine . Though challenging to study in humans, the rise of spectroscopy provides intriguing possibilities for future investigations …”
Section: Future Directionsmentioning
confidence: 99%
“…First, we focused on middle-aged females who were within 10 years of their final menstrual period, as women are at risk of executive dysfunction during the menopause transition (Epperson et al, 2015; Shanmugan and Epperson, 2014; Shanmugan et al, 2017b). Given the impact of estradiol on prefrontal cortex structure and function (Shanmugan and Epperson, 2014) as well as evidence for sex differences in the effects of early adversity (Shanmugan and Satterthwaite, 2016) on neural response, these data cannot be extrapolated to similar-aged males or pre-menopausal females.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that healthy women with no history of cognitive dysfunction experience increased difficulty with everyday tasks requiring executive processes such as working memory, focus, attention, organization, and planning (Epperson et al, 2015; Shanmugan and Epperson, 2014; Shanmugan et al, 2017b). There is preliminary evidence for adverse childhood experiences (ACE) such as abuse, neglect, and household dysfunction as a risk factor for executive dysfunction during this hormonal transition (Shanmugan and Epperson, 2014).…”
Section: Introductionmentioning
confidence: 99%